Burden of Geriatric Events Among Older Adults Undergoing Major Cancer Surgery. Issue 7 (July 2016) - Tan, Hung-Jui; Saliba, Debra; Kwan, Lorna; Moore, Alison A.; Litwin, Mark S.
Abstract : (Abstracted from J Clin Oncol 2016;34:1231–1238) More than half of new cancer cases in the United States occur in older adults 65 years or older. By midcentury, the number of older adults 65 years or older will double, leading to a nearly 50% increase in the annual incidence of cancer.